Simulating Study on Mechanical Properties of Rock Wool Board for Thermal Insulation on External Walls - Xiaoguang Li; Jinjin Liu; Xin Fan; Jinyi Qin; Rui Zhang; Ren Cao; Panqi Wang; Xiaoliang Huo (Advances in Materials Science and Engineering)
Rock wool board (RWB) is widely used in construction of exterior insulation worldwide. Fiber diameter, solid volume fraction (SVF), and contact degree among the fibers significantly influence the RWB physical properties. Herein, the effects of these factors on the mechanical properties of RWB were investigated using the GeoDict software. First, the fiberization process resulted in a finer fiber diameter, and the SVF of RWB increased with decreasing pore sizes. In addition, both the fiber diameter and SVF significantly influenced the RWB shear strength. Furthermore, in compliance with the Chinese standards of compression, tensile, and shear strength, the SVF of RWB with a 10.5 μm fiber diameter did not exceed 4.72%, 4.04%, and 5.4%, respectively. The novel method proposed herein can be used for optimizing the RWB manufacturing process.